Thiol metabolism and redox regulation of cellular functions - Pompella, Alfonso; Bánhegyi, Gábor; Wellman-Rousseau, Maria (NATO science series. Life and behavioural sciences ;, 2002)
This volume contains contributions by some of the leading scientists in the field of thiol oxidation/reduction (redox) biochemistry. It is focused on the biological/pathophysiological implications of newly-discovered functions of cellular thiols, such as glutathione in the first place.